Properties of self-compacting geopolymer concrete - Nurudin, M.F. (Trans Tech Publications Ltd, 2015)
High consumption of natural resources, environmental concern of CO2 emission due to cement production and improvement on concrete performance has become a driving force behind the search for alternative materials. An effort made in this regard is the development of self-compacting geopolymer concrete (SCGC). SCGC is a novel material that involves innovation in the production and casting of concrete. It is a type of concrete that does not require compaction for placing it and can be produced by completely eliminating ordinary Portland cement. This paper explores to produce SCGC made with locally available materials by examining its mechanical properties. It deals with the manufacture of fly ash-based SCGC that could achieve 28 days compressive strength of 40 MPa and fulfill the requirements of concrete in both fresh and hardened state. The essential workability properties of freshly prepared SCGC were assessed and the hardened properties including among others compressive strength, splitting tensile and flexural strength were analyzed. The study produced encouraging results and confirmed the production of satisfactory SCGC. The results indicated that SCGC up to 50 MPa of 28-days compressive strength could be produced. Test results showed that the mechanical properties of SCGC are competitive with those of OPC-based conventional concrete. It is anticipated that the outcomes of this study will extend the scope of SCGC and thus generate new opportunities for the construction industry. Â© (2015) Trans Tech Publications, Switzerland.